Systemic Delivery of CRISPR/Cas9 to Hepatic Tumors Using Altered Tropism of Lentiviral Vector in Cancer Therapy - Sungjin Lee; Ahn Hyung Jun (대한화학회 제 127회 학술발표회 및 총회, 2021)
Therapeutic application of CRISPR/Cas9 nucleases remains a challenge due to the lack of efficient in vivo delivery carriers. Here, we examine the ability of lentiviral vectors pseudotyped with hepatitis C virus (HCV)/E1E2 envelope glycoproteins to systemically deliver CRISPR/Cas9 to hepatic tumors in vivo. We demonstrated that systemic administration of E1E2-pseudotyped lentiviral vectors can selectively deliver Cas9 and sgRNA specific for kinesin spindle protein (KSP) to Huh7 tumors in the orthotopic Huh7 mice due to the specific interactions between E1E2 and their cellular receptors. This specific delivery leads to effective KSP gene disruption, potently inhibiting tumor growth. Furthermore, we demonstrated that E1E2-pseudotyping is more suitable for systemic delivery of CRISPR/Cas9 in cancer therapy than vesicular stomatitis virus-pseudotyping, the most widely used pseudotyping, because of stability in human serum, little transduction to DCs, low innate immune response, and cell-specific targeting ability. This study suggests that E1E2-pseudotyped lentivirus carrying CRISPR/Cas9 can substantially benefit the treatment of Huh7 tumors.
Keywords: 렌티바이러스; 간암; 유전자 치료; pseudotyping